Corneal Melt with Perforation Following Topical Mitomycin-C Application in Pterygium Excision - Shashidhar Banigallapati; Akhil Bevara (Delhi Journal of Ophthalmology)
We report a case of corneal melt with perforation due to Mitomycin-C application during Pterygium excision. A 50-year-old male presented with sudden gross diminution of vision and pain in the left eye since one day. He underwent primary Pterygium excision using a bare sclera technique combined with application of Mitomycin-C to the scleral bed intra-operatively in the left eye 40 days back elsewhere. At the site of pterygium head excision, the cornea showed a 3 × 3 mm perforation with iris prolapse through it. Patient was diagnosed as Corneal perforation post Mitomycin-C application and an immediate full thickness corneal patch grafting was performed in the left eye.